RANCANG BANGUN ABSORBER AMMONIA (DITINJAU DARI LAJU ALIR, TINGGI PACKING DAN VARIASI PACKING TERHADAP KONSENTRASI AMMONIA) - Dwi Nugroho, Afrian; Sabrina, Delanisa; Agustin Pratiwi, Ines; Yerizam, Muhammad; M, Anerasari (KINETIKA, 2021)
The formulation of the problem in this study is how to design an absorber device (in terms of flow rate, packing height, and packing variation to ammonia concentration). This study aims to obtain 1 unit of ammonia absorber, reduce ammonia gas levels with an ammonia absorber and get the effect of H2O flow rate, packing height and packing variations on NH3 concentrations. The data analysis used was univariate analysis and bivariate analysis. The data collection technique used was purposive sampling. The research resulted in 1 unit of ammonia absorber with a tower diameter of 3.5 cm and a tower height of 60 cm. The results showed that the effect of H2O flow rate on ammonia concentration was very influential, it was found that the NH3 concentration value on packing height, namely: at the lowest height of 5 cm the amount of NH3 concentration was 5.9690 N and at a height of 60 cm the amount of NH3 concentration was 4.7518 N. The higher the packing height, the lower the NH3 concentration value, the NH3 concentration value obtained on the packing variation, namely: marbles packing of 4.198 N, stainless steel packing of 2.026 N and packi